Residual Stress Characterization and Control in the Additive Manufacture of Large Scale Metal Structures - Williams, Stewart W.; Colegrove, Paul A.; Ganguly, Supriyo (Materials Research Forum LLC, 2016)
Additive Manufacture of metals is an area of great interest to many industrial sectors. All metal additive manufacturing processes suffer with problems of residual stresses and subsequent distortion or performance issues. Wire + Arc Additive Manufacture (WAAM) is a metal additive manufacture process that is suitable for the production of large scale engineering structures. Paramount to the successful industrial application of WAAM is the understanding and control of residual stress development and their subsequent effects. Vertical inter-pass rolling can be used to reduce these residual stresses, but its potential is limited due to the absence of lateral restraint of the wall. So it deforms the wall in its transverse direction rather than reducing longitudinal tensile residual stresses, which is the main source of the distortion. The potential of a new pinch-roller concept is currently being investigated at Cranfield University with very promising preliminary results: It was possible to entirely eliminate the distortion of a Ti 6Al 4V WAAM wall.
Keywords: Additive Manufacturing; Neutron Diffraction; Contour Method; Cold Rolling; Pinch Rolling